Integration of Mobile Learning in Rifdarmon Model to Improve Student Learning Outcomes - Rifdarmon; Ganefri; Remon Lapisa; M. Giatman; Nizwardi Jalinus; Hasan Maksum (International Journal of Interactive Mobile Technologies (iJIM), 2024)
Mobile learning utilizes mobile technology, such as smartphones, tablets, and other mobile devices, to facilitate a flexible and collaborative learning process. This research aims to implement the integration of mobile learning into the Rifdarmon model in the learning process and evaluate the effectiveness of mobile learning integration into the Rifdarmon model in improving student learning outcomes in the Sensors and Transducers course. This research uses a quantitative approach with an experimental method. The subjects in this study are active students in the Automotive Engineering Department of Padang State University taking the Sensors and Transducers course. The sampling technique used is cluster random sampling, where the researcher randomly selects two classes, the control and experimental classes. Then all students in the selected clusters become the sample. The data in this study were collected based on the pre-test and post-test scores obtained by students in the Sensors and Transducers course. Based on the results and discussion, the implementation of mobile learning integration into the Rifdarmon model in the learning process was successfully carried out in this research. There was a significant increase in learning outcomes for students after following the learning process, both with the conventional learning model (control class) and mobile learning integration into the Rifdarmon model (experimental class).